INOVASI BRIKET GULA AREN SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH PRODUK LOKAL DAN PENGUATAN UMKM DI DESA GELANGSAR - Baiq Aisya Junia Padma; Nugroho, Muhammad Iqbal; Oktariani, Baiq Rara; Pambudi, Dimas Nugroho; Suliyani, Shinta Rahmata; Putra, Lalu Muhammad Bagus Oktora Ramadhan; Santika, Selfi; Wulandari, Wulandari; Giska, Giska; Maharani, Afifah Putri; Lestari, Retno Dita; Puspitasari, Candra Eka (Jurnal Pepadu, 2025)
Gelangsar Village, located in West Lombok Regency, holds significant local potential through its aren (palm sugar) commodity, which serves as the main livelihood for its residents. However, limited product diversification and market access have resulted in low added value. This study aims to describe the implementation of aren sugar briquette innovation as a strategy to enhance economic value and empower local Micro Small and Medium Enterprises (MSME) actors. A descriptive qualitative approach was used through a series of activities including observation, socialization, technical training, and participatory evaluation conducted during the Community Empowerment Community Service Program (KKN PMD) by Universitas Mataram (July–August 2025). The target of the program was farmer groups and MSMEs involved in aren sugar production in Gelangsar. The training results showed that the innovation improved participants' understanding of product diversification and enhanced their skills in production and packaging. Significant impacts were observed across three dimensions: economic (increased selling value and distribution potential), social (strengthened collaboration and youth engagement), and environmental (waste reduction and production efficiency).. These findings highlight the importance of participatory and contextual approaches in driving village-level innovation based on local potential. This program holds promising potential for replication in other areas with similar characteristics.